Design of fire detectors capable of self-adjusting by ignition - Pospelov, Boris; Andronov, Vladimir; Rybka Evgenіy; Skliarov, Stanislav (Eastern-European Journal of Enterprise Technologies, 2017)
The concept of guaranteed ignition detection at a site was introduced. A criterion of optimization of guaranteed detection was formulated, which comes down to the equality of probabilities of false detection and missing of ignition source. Algorithms and structure of fire detectors, capable of self-adjusting by ignition of materials, were developed. Their distinctive feature is the possibility of being applied under uncertain conditions for arbitrary and combustible materials that are unknown in advance. To enhance effectiveness of fire detectors capable of self-adjusting by combustion of materials, we proposed adaptation of original threshold value to current observations of ignition components. For this purpose, it was proposed to use the procedure of median filtration of recorded data. As a parameter of convergence of the procedure of threshold self-adjustment, we consider a fixed and dynamic way of its determining. This makes it possible to provide adjustment of original convergence of procedures toward observed components of combustion of various materials. Verification of the proposed self-adjusting fire detectors indicates their capability to provide guaranteed detection of sources of ignition for various materials at the early stages under conditions unknown in advance